AN ECONOMIC APPRAISAL OF THE RUBBER PROCESSING INDUSTRY IN BENDEL, OGUN AND ONDO STATES OF NIGERIA (1977)
This study attempts to assess the economic performance of the rubber processing industry in Bendel, Ogun and Ondo States of Nigeria. The Nigerian rubber industry which experienced a boom in the early 1950's started to face some serious set-backs during and after the civil war which broke out in 13G7. This set-backs were manifested in form of declining productivity and consequent decline in its contribution to foreign exchange earnings. The study which covers the period 7-1 assesses the economic performance of some rubber processing firms in the three states mentioned above in order to identify some of the factors responsible for the set-backs in the industry. The data used for the study were collected mainly through the use of questionnaires and personal interviews. Other sources of data include Federal office of statistics and ministries of Agriculture and Natural Resources in all the three states. Chapter 1 assesses the economic importance of rubber industry in terms of foreign exchange earnings, employment generation and value added to the Nigerian economy. The rubber industry contributed 6.2 percent of the country's total export earnings in 1363. By 1972, it accounted for 4.7 percent of the country's industrial labour force and Chapter 6 uses non-parametric statistical technique to assess the factors limiting expansion and economic performance of the industry. The major limiting factors are lack of capital and inadequacy of raw materials. Labour is not a limiting factor although the industry i9 short of skilled and managerial personnel. A financial analysis for the industry and the estimation of a profit function for rubber processing industry were the major highlights of chapter seven. The financial analysis shows some weak points in financial management positions of some firms while the profit function shows that volume of sales, and selling expenses are the two major factors affecting profits in the processing industry. Some policy recommendations were advanced and these include the need for individual processors to strive to make use of their under-utilized capacity instead of plant expansion. Also, each processor must upgrade his management capability. The rubber commodity board should (i) appoint a committee to look into the present state of affairs of the rubber industry, establish rubber lumps marketing centres and make provisions for price incentives to producers of natural rubber at all levels.